'Human no like smart ape': figuring the ape as legal person in Rise of the Planet of the Apes. Issue 2 (2nd July 2016) - Hamilton, Sheryl N.
Abstract : This article reads the film Rise of the Planet of the Apes (2011) in the context of popular and legal debates about great ape personhood in order to explore two foundational limits in law's vision of the person. More specifically it explores the figuration of the film's chimpanzee protagonist, Caesar. First, Caesar's 'becoming person' within the narrative demonstrates that rather than a natural, teleological outcome or a benevolent gift from an enlightened sovereign, the status of legal person is often wrested from dominant power formations through organised violence. Second, while awarded personhood in the story, as a chimeric entity, a hybrid of nature and culture, Caesar reveals a second violence: the disciplining, 'civilising' and erasure of animalism required for admittance into the category. The film thus exposes the contemporary untenability of the non-human animal person and illuminates limits in law's imagination.